Quasi-harmonic analysis of fortnightly suspended sediment response to semi-diurnal tidal currents - Zhu, Zichen; Liang, Bingchen; Chen, Bin; Yang, Bo; Chi, Wanqing; Xu, Hao; Hu, Zejian (Frontiers in Marine Science, 2024)
Introduction The suspended sediment concentration (SSC) is an important consideration in marine engineering. Sediment movement characteristics can be studied by considering the fortnightly behavior of SSC. However, this consideration currently lacks accurate mathematical representation. Method In this study, a computationally efficient mathematical model capable of providing analytical solutions for predicting SSC based on resuspension, deposition, and advection was developed to further investigate the mathematical interpretation of fortnightly SSC behavior in coastal areas dominated by M2, S2, O1, K1, M4 and MS4 tides. The model decomposed the SSC into 35 quasi-harmonic terms as well as two terms with fortnightly period. Result The model was applied at five observation sites in the Bohai Sea, Yellow Sea and East China Sea, China, and validated to be able to reproduce the fortnightly variation of SSC. The results show that the primary fortnightly SSC term was generated by the combined action of M2 and S2 tidal currents and had a tidal frequency of 1.0159 °/h, which was equal to the difference between the frequencies of the two partial tides. Discussion The resuspension properties only affected the amplitude of the fortnightly SSC term but did not affect the phase. The deposition properties affected both amplitude and phase. The quasi-harmonic analysis indicates that in certain shallow sea areas with strong nonlinear tidal interactions, the amplitude of the M4 tidal elevation can influence the mean SSC, while the amplitude of the MS4 tidal elevation can affect the fortnightly SSC amplitude. As the simplified model is based on certain assumptions, the application conditions of the quasi-harmonic analytical solution include an approximate reciprocating flow pattern, a tidal range significantly smaller than the water depth. Our results provide a mathematical solution for the fortnightly evolution of suspended sediment.